NATURAL CONVECTION FROM SINGLE FINNED TUBE IMMERRSED IN A TILTED ENCLOSURE (Journal of Engineering, 2006)
Heat transfer rates of a single horizontal finned tube immersed in water –filled enclosure tilted at 30 degrees are measured .The results serve as a baseline case for a solar water heating system with a heat exchanger immersed in integral collector storage. Tests were made with both adiabatic and uniform heat flux boundary conditions. Natural convection flow in enclosure is interpreted from measured water temperature distributions. Formation of an appropriate temperature difference that drives natural convection is determined .Correlations for the overall heat transfer coefficient in terms of the Nusselt and Rayleigh numbers are reduced to the form Nu=0.716 Ra 0.247 Based on the diameter of the immersed tube .Comparison the present workresults with others gave a good agreement